Arquiterura para desenvolvimento de jogos com o uso de componentes reaproveitáveis - Maia, Carlos Edmilson da Silva (2010)
Game development presents more challenges as this type of software becomes more complex and detailed. As in the development of traditional software, this growth in scope incurs in a development process that costs more and has a longer production time, increasing the risks faced by companies that wish to enter or maintain themselves in the electronic game market. With this, it becomes increasingly desirable to search and implement tools that allow for the reduction of required resources to develop games. It is also noticeable that there is an increasing need to proved development teams with new tools that allow faster creation of prototypes, enabling them to test and evolve new game ideas in a nimbler and less expensive way. This work presents the project and implementation of a modular platform that aims to solve or lessen the aforementioned problems, offering a tool that allows for the development of games with reduced costs, in addition to simplifying the quick prototyping process. Through the use of a programming approach based on reusable software components written in different programming languages, this work aims to enable methodologies that are able to foster code reuse, to facilitate team work, to reduce development time and to improve the quality of the final product.